Development of Light-Responsive Poly(γ-Benzyl-L-Glutamate) as Photo Switches by a One-Step NCA Method - Chen, Pin; Kong, Jingyang; Wang, Xin; Ma, Weiye; Yang, Xia; Qin, Yuqing; Hu, Xiaohong (Frontiers in Chemistry, 2020)
Synthesized polypeptide is attracting an increased interests due to its excellent biological characteristic and adjustable chemical properties in bio-related fields. But polypeptide itself has no switching properties, which is harmful to the development of its application as a control component. Herein, light-responsive poly(γ-benzyl-L-glutamate)s (PBLGs) is synthesized by a one-step NCA method using p-aminoazobenzene (m-AZO) and p-diaminoazobenzene (m-DAZO) as initiators. PBLGs exhibit amorphous characteristics with obvious Tg transition, which are 14°C for PBLG1 and 21°C for PBLG2. In order to forecast the structure-property information of PBLGs, theoretical UV-vis spectra as well as the energy gap between HOMO and LUMO is calculated by DFT calculation. Experimental results of UV-vis spectra exhibit similar characteristics to those of theorical UV-vis spectra except for the 40–50 nm red-shifting of absorbance peak. Furthermore, the absorbance intensities of PBLGs have a good linear relationship with their concentration, but their linearity range depending on concentration is completely different. Then, trans–cis transition under a different excitation source and cis–trans recovery in a dark environment are tracked in real-time by UV-vis spectra to evaluate the light response performances. It is found that UV light is the only effective excitation source for PBLG1, and blue light is another effective excitation source for PBLG2 besides UV light. Furthermore, the addition of alcohol and water as cosolvents has little effect on trans→cis transition in UV-light-excited systems, but it shortens recovery time of the cis→trans process in a dark environment. By contrast, the detectable isomerization process becomes unclear with the addition of alcohol in blue-light-excited system. Furthermore, either alcohol or water in solvents accelerate both the trans→cis and cis→trans process in a blue-light-excited system.